2015
DOI: 10.1038/jid.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Melanoma Cell Subpopulations: Their Heterogeneity and Differential Responses to Treatment

Abstract: Metastatic melanoma is a highly heterogeneous tumor; thus, methods to analyze tumor-derived cells circulating in blood should address this diversity. Taking this into account, we analyzed, using multiparametric flow cytometry, the co-expression of the melanoma markers melanoma cell adhesion molecule and melanoma-associated chondroitin sulphate proteoglycan and the tumor-initiating markers ATP-binding cassette sub-family B member 5 (ABCB5), CD271, and receptor activator of NF-κβ (RANK) in individual circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(125 citation statements)
references
References 28 publications
(38 reference statements)
13
111
0
1
Order By: Relevance
“…Using this approach we provided for the first time, a detailed insight into the diversity of MelCTCs within each patient, and showed that the prognostic utility of MelCTCs may not rely on the total count of CTCs but on the CTC subpopulations circulating within an individual. This study indicated that a high number of MelCTCs express melanomainitiating or stem cell markers (ABCB5 and RANK) while only very low numbers of CTCs express melanoma markers MCSP and MCAM [25]. Importantly, the common expression of these melanomainitiating markers by MelCTCs did not correlate with the expression of these markers in patient-matched tumors, where a low frequency of melanoma tumor cells positive for these markers was observed.…”
Section: Melanoma Ctc Detection Methodsmentioning
confidence: 77%
See 4 more Smart Citations
“…Using this approach we provided for the first time, a detailed insight into the diversity of MelCTCs within each patient, and showed that the prognostic utility of MelCTCs may not rely on the total count of CTCs but on the CTC subpopulations circulating within an individual. This study indicated that a high number of MelCTCs express melanomainitiating or stem cell markers (ABCB5 and RANK) while only very low numbers of CTCs express melanoma markers MCSP and MCAM [25]. Importantly, the common expression of these melanomainitiating markers by MelCTCs did not correlate with the expression of these markers in patient-matched tumors, where a low frequency of melanoma tumor cells positive for these markers was observed.…”
Section: Melanoma Ctc Detection Methodsmentioning
confidence: 77%
“…Based on our previous identification of heterogeneous MelCTCs [21], we recently developed a flow-cytometry multimarker approach to detect and analyze CTCs for the presence of melanomaassociated markers, such as MCSP and MCAM, in combination with melanoma stem cell markers, such as ABCB5, RANK (receptor activator of NF-kb) and CD271 [25]. Using this approach we provided for the first time, a detailed insight into the diversity of MelCTCs within each patient, and showed that the prognostic utility of MelCTCs may not rely on the total count of CTCs but on the CTC subpopulations circulating within an individual.…”
Section: Melanoma Ctc Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations